Comparison of Raised IOP after Pars Plana Vitrectomy (Ppv) Using 1000 cSt and 5000 cSt Silicone Oil in Rhegmatogenous Retinal Detachment - Muhammad Nasir Bhatti, Asif Mashood Qazi, Azizur Rahman, Munawer Hussain, Muhammad Fayaz Mazharul Hassan (Pakistan Journal of Ophthalmology, 2011)
Purpose: To compare raised intraocular pressure after pars plana vitrectomy using 1000 cSt and 5000 cSt silicone oil. Materials and Methods: This Interventional quasi experimental study was conducted at Isra Postgraduate Institute of Ophthalmology, Al-Ibrahim Eye Hospital, Malir, Karachi; from January 2008 to June2008.Study included total 60 eyes of 60 patients fulfilling the inclusion criteria. All cases were worked up according to the protocol. After examination, patients were divided into two groups. Group A were injected with 1000 cSt silicone oil and group B were injected with 5000 cSt silicone oil on randomized basis. Patients were followed up at 1st day 1st week, 2nd week, 1st month, 2nd month 3rd month and 6th month. Complete eye examination including IOP measurement was done on each visit. Data analysis was done by SPSS version 10.0 Results: Over a follow up period of 6 months, there was no significant difference in raised intraocular pressure after using 1000 cSt and 5000 cSt silicone oil injection. Conclusions: Difference in IOP was observed between the study groups on three months follow-up. However, there was no significant difference in raised intraocular pressure after 6 months of the intervention.